2018
DOI: 10.1088/1361-6528/aaea3a
|View full text |Cite
|
Sign up to set email alerts
|

TSV-integrated thermoelectric cooling by holey silicon for hot spot thermal management

Abstract: The trends toward higher power, higher frequency, and smaller scale electronics are making heat dissipation ever more challenging. Passive thermal management based on high thermal conductivity materials or through-silicon vias (TSVs) may not provide sufficient cooling for hot spots reaching 1 kW cm−2, and active thermal management by thermoelectric cooling (TEC) may require large power consumption or suffer from a large off-state thermal resistance of thermoelectric materials. Here we address these issues by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…However, this maximum value requires limiting dimensions of ∼20 nm, where achieving bulk like electrical conductivity is challenging. The data and modeling presented here are useful in the design of future thermoelectric devices such as Peltier coolers based on nanostructured silicon 31,32 . Finally, we note that the loss of phonon drag is inconsequential at high temperatures (> 600 K) where drag is absent even in the bulk due to Umklapp scattering.…”
Section: Discussionmentioning
confidence: 99%
“…However, this maximum value requires limiting dimensions of ∼20 nm, where achieving bulk like electrical conductivity is challenging. The data and modeling presented here are useful in the design of future thermoelectric devices such as Peltier coolers based on nanostructured silicon 31,32 . Finally, we note that the loss of phonon drag is inconsequential at high temperatures (> 600 K) where drag is absent even in the bulk due to Umklapp scattering.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, silicon nanostructures with vertically etched holes, or holey silicon, had demonstrated significant thermalconductivity reductions and anisotropic thermal conductivity in the in-plane and cross-plane directions [56][57][58]. Ren and Lee had shown that the unique thermal-conductivity anisotropy in holey silicon is ideal for thermoelectric cooling (TEC) to address onchip hot spots [59,60]. In the in-plane direction, the neck size dominated phonon boundary scattering reduces the thermal conductivity (k x and k y ), which sustains a large temperature gradient for enhanced thermoelectric effects.…”
Section: Recent Progress In Thermal Metamaterialsmentioning
confidence: 99%
“…In the last decade, the thermal models of TSV, coaxial TSV, and TSV arrays have been systematically investigated and established [15,16]. Meanwhile, the thermal models of 3D ICs have also been studied [17][18][19].…”
Section: Introductionmentioning
confidence: 99%